The Burden of Asymptomatic Malaria Infection in Children in Sub-Saharan Africa: A Systematic Review and Meta-Analysis Exploring Barriers to Elimination and Prevention - Daniel Asmelash; Wubetu Agegnehu; Wondaya Fenta; Yemane Asmelash; Shibihon Debebe; Abyot Asres (Journal of Epidemiology and Global Health)
Abstract Background Malaria remains a major public health problem that continues to cause death in under-five children nearly every minute. The purpose of this systematic review and meta-analysis was to determine the pooled prevalence and predictors of asymptomatic malaria in children in Sub-Saharan Africa. Methods Relevant studies were retrieved from Web of Science, Cochrane Library, PubMed, Google Scholar, Gray Literature, Embase, and African Online Journal databases published between 2014 and 2024. Data quality was assessed by a tool developed by Hoy and colleagues and classified as low, moderate, or high risk of bias. We performed a random effects model and sub-group analysis by age group, region, and diagnostic methods. The protocol was registered in the PROSPERO (CRD42024584354). Results A total of 24 cross-sectional studies with 19,169 participants from 10 Sub-Saharan Africa countries were included in the analyses under the age of 15 years. The overall prevalence of asymptomatic malaria was 25% (95% CI: 20–30%) and showed no evidence of publication bias. Utilization of insecticide-treated nets was significantly associated with asymptomatic malaria. In addition, the overall prevalence of anemia in asymptomatic Plasmodium-infected children under the age of 15 was found to be 35% (95% CI: 24–46%). Subgroup analysis showed significant regional and diagnostic tool differences in asymptomatic Plasmodium infection. Conclusion The findings of this study revealed a high prevalence of asymptomatic plasmodium infection in children with significant regional variations. There was a significant association with anemia and the utilization of insecticide-treated nets.